2022
DOI: 10.3389/fphar.2021.808797
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-8 in Lung Inflammation and Injury: Implications for the Management of COVID-19 and Hyperinflammatory Acute Respiratory Distress Syndrome

Abstract: Severe Acute Respiratory Syndrome Coronavirus—2 (SARS CoV-2) has resulted in the global spread of Coronavirus Disease 2019 (COVID-19) and an increase in complications including Acute Respiratory Distress Syndrome (ARDS). Due to the lack of therapeutic options for Acute Respiratory Distress Syndrome, recent attention has focused on differentiating hyper- and hypo-inflammatory phenotypes of ARDS to help define effective therapeutic strategies. Interleukin 8 (IL-8) is a pro-inflammatory cytokine that has a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 76 publications
4
73
0
1
Order By: Relevance
“…Although all these preliminary studies were performed with a limited number of patient samples, our findings agree with these reports, demonstrating robust production of the neutrophilchemoattractant chemokine CXCL8 as a universal COVID-19 mediator in systemic and airway compartments. Thus, the present and previous finds are indicative that CXCL8-neutrophil axis would be a putative target for therapeutic interventions (26).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although all these preliminary studies were performed with a limited number of patient samples, our findings agree with these reports, demonstrating robust production of the neutrophilchemoattractant chemokine CXCL8 as a universal COVID-19 mediator in systemic and airway compartments. Thus, the present and previous finds are indicative that CXCL8-neutrophil axis would be a putative target for therapeutic interventions (26).…”
Section: Discussionsupporting
confidence: 66%
“…Significant elevation of CXCL8, which is a classic neutrophil activation and chemoattractant mediator indicates the presence of these polymorphonuclear cells as pivotal driver of the immunopathogenesis in COVID-19 (14,(25)(26)(27)(28)(29). In line with this hypothesis, neutrophils have been found as important conspirators of morbid thrombotic events and severe COVID-19 by the formation of neutrophil extracellular traps (NETs) (28).…”
Section: Discussionmentioning
confidence: 87%
“…Because lack of therapeutic options for tackling acute respiratory distress syndrome (ARDS) in COVID-19 patients, attention has now focused on differentiating hyper- and hypo-inflammatory phenotypes of ARDS to help develop effective therapeutic interventions. In this regard, IL-8 which is a pro-inflammatory cytokine performs an important role in neutrophil activation and has been identified for the progression of COVID-19 disease [ 83 , 84 ]. Furthermore, it has been reported that COVID-19 patients with severe outcome also display higher plasma levels of chemokines such as CXCL9/MIG, CXCL8/IL-8, and CXCL10/IP10 along with cytokines IL-6 and IL-10 than the patients with the milder form of the COVID-19 [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…This evidence suggests that, in LAM, senescent LAM cells might reduce the proliferation of lung resident cells and, at the same time, might promote a pro-inflammatory microenvironment that ultimately has detrimental effects on the lung tissue. Indeed, even if IL-8 has a clear role as a SASP molecule, its secretion by fibroblasts, alveolar macrophages, and alveolar cells and its involvement in neutrophil migration and infiltration in lungs suggest a more complex physiological implication, making the deregulation of IL-8 secretion responsible for pathological processes, i.e., in IPF [25], acute respiratory distress syndrome [26], and chronic obstructive pulmonary disease [39]. Besides the crucial role of IL-8 in lung inflammation, little is known concerning its involvement in LAM or TSC.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is a chemokine overexpressed in the most senescent cells as a SASP component and its high levels in lung parenchyma have been related to the pathogenesis and progression of lung diseases, such as IPF [25]. IL-8 is expressed in various cell types, including fibroblasts, and is highly secreted by LAM/TSC cells [16,26]. The mRNA relative expression and the secretion of IL-8 were significantly higher in LAM/TSC cells compared to PLFs suggesting a SASP IL-8 role in sustaining LAM/TSC cell senescent phenotype (Figure 7a,c).…”
Section: Evaluation Of Il-8 Expression and Secretion In Plfs Lam/tsc ...mentioning
confidence: 99%